Chipmunk at Hollow Tree Lane - Sherrow, Victoria; Davis, Allen (Norwalk, Conn. : Soundprints, 1994)
Describes how Chipmunk gathers and stores food to prepare for winter.
Accelerated Reader AR
Keywords: Chipmunks -- Juvenile fiction; Chipmunks -- Fiction